Central precocious puberty and granulosa cell ovarian tumor in an 8-year old female - Valeria Calcaterra; Ghassan Nakib; Gloria Pelizzo; Barbara Rundo; Gaetana Anna Rispoli; Stella Boghen; Federico Bonetti; Barbara Del Monte; Chiara Gertosio; Daniela Larizza (MDPI AG, 2013)
Ovarian tumors associated with hormonal changes of the peripheral iso-sexual precocious puberty are of common presentation. We describe here a rare case of juvenile granulosa cell tumor in a female with central precocious puberty (CPP). An 8-year old girl with CPP presented with vaginal bleeding four months after the diagnosis and before starting treatment with gonadotropin-releasing hormone (GnRH)-analogs. Suppression of basal follicle-stimulating hormone (FSH) level, elevation of serum estradiol, progesterone and Cancer Antigen-125 were documented. Abdominal ultrasound examination (US) and magnetic resonance imaging showed a pelvic mass affecting the left ovary. A left salpingo-oophorectomy was performed and the mass was totally resected. Juvenile granulosa cell ovarian tumor was diagnosed. One month post surgery, estradiol and progesterone decreased to values of the first evaluation and FSH increased; Cancer Antigen-125 resulted normal while ultrasound pelvic examination showed absence of pelvic masses. In our patient, the tumor had grown very quickly since hormonal data demonstrated a CPP without any evidence of ovarian mass on US only four months before diagnosis. The overstimulation of the FSH or aberrant activation of FSH receptors may have contributed to the development of the mass.